Using Theory to Understand the Barriers to Engagement in Group Offending Behavior Programs - Holdsworth, Emma (International journal of offender therapy and comparative criminology, 2019)
Noncompletion of group offending behavior programs is a common problem, indicating barriers to engagement. While existing theoretical models have accounted for determinants of motivation, little focus has been directed towards barriers to engagement. The authors developed the program engagement theory (PET) which not only accounts for the determinants of engagement and the engagement process, it also considers the barriers to engagement. Interviews and session observations were used to collect data from 23 program facilitators and 28 offenders, which were analyzed using grounded theory. The barriers to engagement were classified as program and referral factors (uninformative referrals, offense-focused programs, rigid and abstract content, didactic delivery, and homework), facilitator characteristics (lack of control: contentious and nonassertive), and group member characteristics (unmotivated, pre-contemplative, and blaming others and young, chaotic, and disruptive). Suggestions as to the design and facilitation of group offending behavior programs, and facilitator training and supervision to overcome barriers to engagement are proposed.